Benign cause of neck pain: Case report on acute calcific tendinitis of longus colli muscle - Muhammad Zahid Abdul Muien; Alvin Oliver Payus; Yong Guang Teh (Elsevier, 2022)
Acute calcific tendinitis is a rare cause of acute neck pain that is attributed to calcium hydroxyapatite deposition in the longus colli tendon. It is usually associated with pre-vertebral effusion. Acute calcific tendinitis is a non-infectious cause of inflammation, mimicking a more sinister disease such as retropharyngeal abscess, trauma, or oro-pharyngeal neoplasm. Findings in the contrasted computed tomography include the characteristic sign of calcification in the attachment of the longus colli tendon predominantly at the C1 and C2 level, non-enhancing retropharyngeal fluid, and the absence of retropharyngeal nodes. We present a case of a 51-year old gentleman, who presented with an acute history of neck pain, dysphagia, and odynophagia. There were no clinical signs of infection. Flexible scope reveals bulging of the retropharyngeal space with normal mucosa. Computed tomography reveals calcification of the longus colli tendon at the level of C1 with fluid collection in the retropharyngeal region. The patient was treated conservatively and the follow-up scope revealed normal findings. Recognition of the characteristic imaging appearance allows accurate diagnosis preventing unnecessary tests, imaging, and treatment. In conclusion, although most neck pain is due to a common cause, it is still particularly important to correlate the laboratory and radiological investigations to determine other uncommon causes to prevent unnecessary intervention for the patient.